Sustainable Urban Agricultural Land Protection Policy: The Case of Surakarta City, Central Java Province, Indonesia - FX Andy Sutrisno; Bakti Setiawan (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
This study highlights Indonesia’s sustainable agricultural land protection policy, especially the issue of conservation within the urban environment. This study aims to assess the Surakarta Local Government policy for the protection of urban agricultural land and to explore the perceptions of urban farmers and agricultural landowners in responding to the policy. This research is expected to bridge the gap between the policy and the interests of farmers and agricultural landowners. This research is based on a case study. Data and information were gathered through field observations, interviews with various stakeholders and secondary data collection. This study found that the policy is not well understood by farmers and landowners, who are the directly affected party. Moreover, the local government actually views urban agricultural land from an economic standpoint and tends to be less supportive of this conservation effort. Instead, farmers and agricultural landowners are the ones who believe that this policy is essential. Nevertheless, they reject the policy because they must relinquish some rights to their land after it has been designated as sustainable urban agricultural land. Another shortcoming is that the promised incentives are not economically sufficient to compensate them for their efforts in protecting the agricultural land. The study recommends progressive policies to reduce the gap between the policy’s intentions and the interests of farmers and agricultural landowners, as well as to respond to the obstacles that may arise in the implementation of the policy. It is intended that the purpose of conservation and food security be achieved, without harming the farmers’ or agricultural landowners’ rights.